Exploration of private higher education research in Saudi Arabia: a bibliometric analysis / Mohammed M. Bsiso and Majid Ghasemy - M. Bsiso, Mohammed; Ghasemy, Majid (Universiti Teknologi MARA, 2024)
Private higher education has expanded significantly in Saudi Arabia over the past two decades. This was driven by the desire to achieve world-class higher education and the need to address an increasingly expanding student population seeking to obtain the qualifications needed to enter the quickly modernizing Saudi job market. Naturally, research on higher education in Saudi Arabia has also become more common, with thousands of publications added over the past few years. However, it is not clear what portion of this research has focused on private higher education. Additionally, it is not clear what knowledge gaps exist in private higher education research in Saudi Arabia. This study implemented a bibliometric analysis to explore the status of private higher education in the body of literature. After conducting a performance analysis, our results showed that from 2002 to 2023, only 103 Scopus-indexed documents were published about private higher education in Saudi Arabia. These results are presented to highlight the main authors, institutions, and subject areas in the field. Afterwards, we comprehensively discuss and analyze the significance of these findings and their implications for Saudi private higher education research. Finally, the study concludes by providing recommendations for advancing research in this critical sector.